MOTIVASI BELAJAR SISWA KELAS XI BDP DI SMK MUHAMMADIYAH 2 PEKANBARU PADA PEMBELAJARAN PJOK SELAMA PANDEMI COVID - Rohim, Muhammad; Wijayanti, Ni Putu Nita; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The purpose of this study was to find out how much motivation to learn for class XI BDP students at SMK Muhammadiyah 2 Pekanbaru in PJOK learning during the covid pandemic. This research was carried out at SMK Muhammadiyah 2 Pekanbaru located on JL. KH. Ahmad Dahlan No. 90 kp. Malay, District. Sukajadi, Pekanbaru City, in March – June 2021 at SMK Muhammadiyah 2 Pekanbaru. This research is a descriptive study that aims to determine how much motivation the students of class XI BDP at SMK Muhammadiyah 2 Pekanbaru are in learning physical education. In this study, the researcher used a questionnaire/questionnaire to collect data. In addition, the questionnaire provides more opportunities for students or respondents to provide good and correct information. Corner learning during the covid pandemic was in the good category with an average score of 100.1 and a percentage of 73.6%.Key Words: Motivation, Learning, Covid Pandemic